Menilik Neuroteologi dalam Perspektif Fides et Ratio - Susanto, Christine (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2022)
For millenia the knowledge of God has become one of the most fundamental quest of the human soul. Man feels God’s calling to search for Him in his innermost being and he responds to it by faith. Through his reason man continously seek to unveil the mystery of God as revealed to him through religion. In today’s world where knowledge is dominated by science and conclusions are reached through positivism, neurotheology emerged as a new way to answer the reality on the existence of God and of the human soul. It uses the scientific findings of neuroscience experiments to conclude that God and the human soul do not exist, that their existence is merely caused by the structures and functions of the human brain. This paper attempts to analyse neurotheology according to the perspective of John Paul II in Fides et Ratio to answer the question of how should the faithful respond to neurotheology which has increasingly become a threat to faith. An underlying error on the rejection of the existence of metaphysics is discussed and a two-winged attitude of critical thinking and openness to faith is proposed to the Christian faithful.